The Contribution of Mass Organization to the Improvement of SMEs Business (A Case Study on KJKS Ankasa GP. Ansor of Pekalongan Regency) - Jumailah Jumailah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
This article aims to find out the contribution of mass organization to the improvement of SME business in KJKS Ankasa GP. Ansor of Pekalongan Regency. This study was a qualitative research with case study approach. The subject of research was Sharia-based Financial Service Cooperatives (Koperasi Jasa Keuangan Syariah, thereafter called KJKS) Ankasa, while the object was GP Ansor of Pekalongan Regency. The result of research showed that GP Ansor of Pekalongan Regency can empower the existing economic potency of members, by means of developing pro-people economy, establishing KJKS. The presence of KJKS can reduce unemployment rate, by providing funding help. The fund grant is given to the members having expertise (skill) but having no capital. To the public, this KJKS Ankasa is a means of providing capital, particularly to small-to-medium scale employers that facilitates them in the term of financing. To GP. Ansor, the presence of KJKS is beneficial to the distribution of fund for social activity (social service) purpose. KJKS Ankasa’s business activity includes financing, investment, and saving corresponding to profit sharing (sharia) pattern and aiming to achieve organizational independency.